1981
DOI: 10.1038/bjc.1981.142
|View full text |Cite
|
Sign up to set email alerts
|

Initiation and promotion at different ages and doses in 2200 mice. II. Decrease in promotion by TPA with ageing

Abstract: Summary.-Using the data described in Paper I, we compare the effects of the same treatment timings and doses given at different ages. Initiation with DMBA at 68 weeks of age, followed 3 weeks later by TPA, has a significantly (P < 0.0001) less rapid effect on subsequent tumour incidence than does initiation at 8 or at 48 weeks of age, followed 3 weeks later by TPA. We suggest that this is chiefly due not to changes in the numbers of cells initiated by DMBA, but rather to a decrease in the promotional efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…This can, however, be caused by the progressive elimination of predisposed (very high risk) individuals at young ages, as suggested also for breast cancer,8, 10, 29, 30 together with some possible under‐reporting at elderly ages, which, however, is unlikely to explain a decline in rates starting at age 55. A fall in rates in the elderly may also be due to some reduction in the ability to respond to promoters, as indicated by animal experiments on mice given initiators and promoters at different times in their life 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…This can, however, be caused by the progressive elimination of predisposed (very high risk) individuals at young ages, as suggested also for breast cancer,8, 10, 29, 30 together with some possible under‐reporting at elderly ages, which, however, is unlikely to explain a decline in rates starting at age 55. A fall in rates in the elderly may also be due to some reduction in the ability to respond to promoters, as indicated by animal experiments on mice given initiators and promoters at different times in their life 32, 33…”
Section: Discussionmentioning
confidence: 99%
“…In this context one could broadly explain an initiatorpromoter experiment by saying that the initiator affects primarily the first step and the promoter primarily a later step (perhaps the second of two). However, Stenback et al (22)(23)(24) have shown that the interpretation of these experiments may be complicated by aging and other effects. Earlier, Peto et al (25) had carried out some experiments with regular benzpyrene applications to mice, which showed that under these circumstances the incidence of tumors depended on the time since start of exposure and not on age.…”
Section: Animal Experiments and The Effects Of Applied Carcinogensmentioning
confidence: 99%
“…However, Stenback et al (22)(23)(24) have shown that the interpretation of these experiments may be complicated by aging and other effects. Earlier, Peto et al (25) had carried out some experiments with regular benzpyrene applications to mice, which showed that under these circumstances the incidence of tumors depended on the time since start with the view that the first stage is affected and that its enhanced event rate in the presence of benzpyrene is much greater than the natural background rate.…”
Section: Ues Of I (Early Stages Affected) What Matters Is the Value mentioning
confidence: 99%